Uppförandekoder inom livsmedelsindustrin : en fallstudie - Jansson, Elin (SLU/Dept. of Economics, 2011)
The world has changed its understanding of environmental issues dramatically and more people are showing awareness of social and environmental problems. Various stakeholders have increasingly begun to show an interest in how companies are taking responsibility for their actions. This has led to an improved activity amongst organizations to make their production consequences positive. They work with Corporate and Social Responsibility (CSR). In order to communicate their responsibilities, many companies work with CSR and ethical guidelines. The guidelines are code of conduct. The Food Industry has noticed the trend of responsibility as more and more stakeholders present their requirements and expectations of the company. Therefore many companies have set up CSR programs which may include adoption of a code of conduct to guide their operation and ethical guidelines as grounds for external communication. If the company is not perceived as accountable by key stakeholders the company may suffer negative consequences. For example, the consumer leaves for another store, the company choose another supplier or that the investor leaves the company’s operation to begin to work with another company. When stakeholder has such strong interest in the companies responsibility work, then the content of the code of conduct increases in importance. The aim of this study is to describe how codes of conduct are enacted. The empirical study shows three companies in the Food Industry works with their codes of conduct. In the study, these three companies’ codes are compared in similarities and differences. Following companies are in focus of this study: Lantmännen, Systembolaget AB and Abba Seafood AB. The companies in this study believe it is important to work with socially- and environmental responsibility and all believe it is important to communicate their positions to their stakeholders. The companies that are in focus for this study have all similar Codes of Conduct which are based on international accepted ethical guidelines. The differences that appear may be because the Codes are tailored to to their business. All case companies have a Code of Conduct for their employee and one concentrated Code of Conduct for their suppliers. Since the companies have worked with CSR before they introduced their Code of Conduct, adopting the Code was a natural step in the companies responsibility work.